Effect brassinolide aplication on growth and physiological changes in two cultivars of fig (Ficus carica L.) - Zulkarnaini, Zulias Mardinata; Sakimin, Siti Zaharah; Tengku Muda Mohamed, Mahmud; Jaafar, Hawa Z. E. (Universiti Putra Malaysia Press, 2019)
Brassinolide (BL) is a plant hormone showing wide occurrence in the plant kingdom with unique biological effects on growth and physiological traits. The fig varieties, Improved Brown Turkey (IBT) and Masui Dauphine (MD), are commonly found in Indonesia and Malaysia. There is limited information on exogenous brassinolide application on these varieties. Thus, the aim of this study is to investigate the effect of different concentration of exogenous application of BL on growth and physiological changes of fig. Fig planting materials were propagated using stem cutting and then transferred into media containing 3:2:1 mixed soil (top soil: organic matters: sand). Two fig cultivars treated with BL (control, 50, 100 and 200 ml.L-1) were arranged as Split Plot Randomized Complete Block Design (SRCBD) with four replications. Plant growth (Plant Height [PH], Total Leaf Area [TLA], Total Dry Biomass [TDB], Specific Leaf Area [SLA], Shoot to Root Ratio [S/R] and Net Assimilation Rate [NAR]) and physiological changes (Photosynthesis Rate [A], Stomatal Conductance [gs], Transpiration Rate [E] and Chlorophyll Content [CC] were investigated every three weeks and at monthly intervals, respectively. Increasing BL concentration (50, 100, and 200 ml.L-1) caused some differences in growth and physiological changes of fig, but the differences were not consistent and most of the changes happened only in first or second month. Cultivar IBT showed higher growth and physiological changes than cultivar MD after receiving brassinolide treatment. There was significant effect of interaction between brassinolide and variety on growth and physiological changes of fig except in the parameters of plant height and total dry biomass.